Turkish adaptation and implementation of the modified infection control questionnaire in intraoral digital imaging - Ilkay Peker; Bulent Altunkaynak; Zuhre Akarslan; Melih Ozdede (Istanbul University, 2021)
Purpose: There are very few studies evaluating the knowledge of dentists about infection precautions in oral radiology. The aim of this study was to assess the psychometric properties of the Turkish version of the modified form of a developed questionnaire and to apply this questionnaire to Turkish dentists. Materials and Methods: The questionnaire was applied to a sample of 250 dentists for the scale development [200 for confirmatory factor analysis (CFA) and 50 for control] and 173 dentists for the implementation of the scale. The scale was applied to 200 dentists and construct validity was examined with CFA. For model fit; 2/df ratio, RMSEA (Root Mean Square Error of Approximation), TLI (Tucker-Lewis Index), CFI (Comparative Fit Index), GFI (goodness of fit index), AGFI (adjusted goodness of fit index) and NFI (normed fit index) were obtained. Also, reliability analysis was applied and item-total correlations and Cronbach's alpha values were given. Adapted scale scores using a different sample of 173 dentists were compared according to demographic characteristics. Results: CFA showed good fit statistics (2/df=1.511, RMSEA=0.057, TLI=0.942, CFI=0.953, GFI=0.926, AGFI=0.900, NFI=0.928) for the scale. Item-total correlations were over 0.30 and Cronbach's alpha was calculated as 0.877. In addition, experienced dentists had higher scores in the dimension of personal hygiene (p < 0.05). Conclusion: The Turkish version of the modified infection control questionnaire in oral radiology showed adequate psychometric properties. This indicated that it could be a valid and reliable tool for the assessment of infection control in oral radiology among Turkish dentists.